Borderline Personality Features, Somatization, and Stress Reactivity: A Biopsychosocial Model - Piskorz-Ryń , Oriana; Flores Carrera , Stephanie; Narcisa Idrovo , Mercedes (Journal of Personality and Psychosomatic Research (JPPR), 2026)
The objective of this study was to examine the relationships between borderline personality features, stress reactivity, and somatization within a biopsychosocial framework and to test the mediating role of stress reactivity in the association between borderline personality features and somatic symptom severity. This study used a cross-sectional correlational design and was conducted in an adult community sample from Colombia. Participants completed validated self-report measures assessing borderline personality features, perceived stress reactivity, and somatic symptoms. Borderline personality features were measured using the Borderline Features scale of the Personality Assessment Inventory, stress reactivity was assessed with the Perceived Stress Scale, and somatization was measured using the Patient Health Questionnaire–15. Data were analyzed using descriptive statistics, Pearson correlation analyses, multiple regression models, and regression-based mediation analyses with bootstrapped confidence intervals to test the proposed biopsychosocial model. Inferential analyses revealed significant positive correlations between borderline personality features and somatization, borderline personality features and stress reactivity, and stress reactivity and somatization. Multiple regression analysis indicated that both borderline personality features and stress reactivity independently and significantly predicted somatic symptom severity. Mediation analysis demonstrated that stress reactivity partially mediated the relationship between borderline personality features and somatization, with a significant indirect effect and a remaining significant direct effect of borderline personality features on somatic symptoms. The findings support an integrated biopsychosocial model in which borderline personality features are associated with increased somatic symptom burden both directly and indirectly through heightened stress reactivity, underscoring the central role of stress-related processes in the embodiment of personality-related emotional vulnerability.